Online Presence System Development Website-Based using Prototype Methods - Muhammad Nur Faiz; Nur Wahyu Rahadi; Nur Wachid Adi Prasetya (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2021)
In the current era of the Covid-19 pandemic, almost all activities use technology, such as the lecture process. Almost all of the lecturing processes in high education are carried out online because it is to reduce the risk of contracting covid-19. The manual presences system by filling out forms or signatures is no longer effective because it has to be done offline. The online presence system is a system that is needed to find out about lectures, the discipline of teaching and students. The method used in the development of this system is Prototype. This method has the advantage of paying close attention to user needs and a faster time for software development. The results of this study are a system for online presence in the era of the Covid-19 pandemic in real-time with photo evidence. Teaching can validate and change the presence of students. In addition, the admin can easily recap the number of teaching and students presences for reporting. Teaching also finds it helpful to take the results of student presences for reporting the completeness of the assessment data and the head of the study program can see the presences summary report online. This system has been tested for functionality with an average result of 83.5% so that it can be said to be successfully built according to user needs